The Impact of Long-Term Education Projects on the Students’ Conceptual Knowledge - Baprowska, Anna; Nodzyńska, Małgorzata (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The article describes research on the impact of long-term education projects on the increase in students’ knowledge (understood as information, skills, attitudes). Two groups of students participated in the project which lasted two years: talented students interested in chemistry and students having problems with this subject. The results obtained show that there was a significant increase in knowledge in both groups. The detailed differences between the two groups are described in the article.